Pembuatan Pin Gantungan Kunci untuk Meningkatkan Kreatifitas Mahasiswa - Rahma; Ikbal; Rahmat, Sahbuddin; Milani, Agus; Sapar (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Utilizing used goods into creative key chain products with selling value is an effort to enhance student creativity. The student-entrepreneurship creativity program (PKM-K) aims to motivate students to become entrepreneurs by processing used goods into marketable key chain products. Key chains are useful for holding keys to prevent them from getting lost. This product also enhances the creative value for entrepreneurs and attracts consumers. The program implementation methods include input, process (production), output, and evaluation. The input stage involves market surveys and feasibility studies, while the process stage involves the production of key chains from material preparation to marketing. The evaluation stage assesses product deficiencies and areas for improvement. The PKM-K program concludes that transforming used goods into marketable key chain products equips students with innovative and creative skills, provides entrepreneurship practice opportunities, and fosters a comprehensive understanding of entrepreneurial concepts.